Pelatihan Penulisan Karya Ilmiah untuk Guru PAUD dan TK di Singkarak Kabupaten Solok: Meningkatkan Profesionalisme dan Keterampilan - Lira, Lira Hayu Afdetis Mana; Harnon; Muhammadi; Lusiana (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
The scientific writing training for early childhood and kindergarten teachers in Singkarak, Solok Regency, aims to enhance the professionalism and writing skills of the teachers. The training was conducted virtually for one day, involving 25 participants. The methods used included lectures, Q&A sessions, group discussions, and practical exercises. Evaluation showed highly enthusiastic and active participation from the teachers, with significant improvement in their scientific writing skills. Evaluation results through writing assignments, satisfaction surveys, observations, and in-depth interviews indicated that participants were able to understand and apply scientific writing techniques more effectively. Technical challenges and varying levels of participant understanding were successfully addressed through an inclusive approach and adequate technical support. The training had a positive short-term impact by increasing the teachers' technical skills and confidence, and it is expected to have a long-term effect on improving education quality through the application of evidence-based teaching practices. Overall, the training significantly contributed to enhancing the professional competence of early childhood and kindergarten teachers in Singkarak. Recommendations for future training include extending the duration, providing individual mentoring sessions, and using more interactive learning media. This training marks an important initial step in efforts to improve the quality of education in the region. Keywords: training; scientific paper; preschool and kindergarten teachers